The zebrafish galectins Drgal1-L2 and Drgal3-L1 bind in vitro to the infectious hematopoietic necrosis virus (IHNV) glycoprotein and reduce viral adhesion to fish epithelial cells. (February 2016) - Nita-Lazar, Mihai; Mancini, Justin; Feng, Chiguang; González-Montalbán, Núria; Ravindran, Chinnarajan; Jackson, Shawn; Heras-Sánchez, Ana de las; Giomarelli, Barbara; Ahmed, Hafiz; Haslam, Stuart M.; Wu, Gang; Dell, Anne; et al.
Abstract: The infectious hematopoietic necrosis virus (IHNV; Rhabdoviridae, Novirhabdovirus) infects teleost fish, such as salmon and trout, and is responsible for significant losses in the aquaculture industry and in wild fish populations. Although IHNV enters the host through the skin at the base of the fins, the viral adhesion and entry mechanisms are not fully understood. In recent years, evidence has accumulated in support of the key roles played by protein-carbohydrate interactions between host lectins secreted to the extracellular space and virion envelope glycoproteins in modulating viral adhesion and infectivity. In this study, we assessed in vitro the potential role(s) of zebrafish ( Danio rerio ) proto type galectin-1 (Drgal1-L2) and a chimera galectin-3 (Drgal3-L1) in IHNV adhesion to epithelial cells. Our results suggest that the extracellular Drgal1-L2 and Drgal3-L1 interact directly and in a carbohydrate-dependent manner with the IHNV glycosylated envelope and glycans on the epithelial cell surface, significantly reducing viral adhesion. Highlights: Exposure to IHNV upregulates galectin expression in fish epithelial cells. Extracellular galectins interact directly with the IHNV glycosylated envelope. Identified galectin oligosaccharide ligands on IHNV responsible for galectin binding. Extracellular galectins significantly reduce viral adhesion to epithelial cells.